Label-free quantitative proteomics of arbuscular mycorrhizal Elaeagnus angustifolia seedlings provides insights into salt-stress tolerance mechanisms - Chang, Wei; Zhang, Yan; Ping, Yuan; Li, Kun; Qi, Dan-Dan; Song, Fu-Qiang (Frontiers in Plant Science, 2023)
Soil salinization has become one of the most serious environmental issues globally. Excessive accumulation of salts will affect adversely the survival, growth, and reproduction of plants. Elaeagnus angustifolia L.,commonly known as oleaster or Russian olive, has the characteristics of tolerance to drought and salt. Arbuscular mycorrhizal (AM) fungi are considered to be bio-ameliorator of saline soils that can enhance salt tolerance of host plants. However, there is little information on the root proteomics of AM plants under salt stress. In this study, label-free quantitative proteomics method was employed to identify the differentially abundant proteins in AM E. angustifolia seedlings under salt stress. The results showed a total of 170 proteins were significantly differentially regulated in E. angustifolia seedlings after AMF inoculation under salt stress, of which 22 were up-regulated, 29 were down-regulated, 50 were not expressed and 69 were newly emerged proteins. Moreover, the salt-stress tolerance mechanisms of AM E. angustifolia may have the following aspects: firstly, regulating the expression of AAT and DEP1 key enzymes can improve the salt tolerance of E. angustifolia in amino acid metabolism, C and N metabolism, K+/Na+ concentration balance, modulation of meristematic activity and cell proliferation, production of secondary metabolites; secondly, regulating the expression of PLD, DGK, and GPAT key enzymes of lipid metabolism can help E. angustifolia in protein kinase signal transduction, cell membrane structure stability, regulation of lipid composition dynamic balance, auxin transport and distribution, plant root growth and development, Na+ efflux, polyunsaturated fatty acid content, calcium signal transduction and other aspects in response to salt stress; thirdly, GGTs, a key enzyme regulating the glutathione metabolism, was differentially expressed to enhance the salt tolerance of E. angustifolia in terms of mitigating oxidative stress by metabolizing GSSG and GS-conjugates and re-synthesizing GSH. In conclusion, these findings provide new insights into the salt-stress tolerance mechanisms of AM E. angustifolia seedlings and also clarify the role of AM fungi in the molecular regulation network of E. angustifolia under salt stress. The research results provide a theoretical basis for the use of AMF and salt tolerant plants to restore saline-alkali land in northern China.